2009
DOI: 10.1073/pnas.0902545106
|View full text |Cite
|
Sign up to set email alerts
|

Aberrantly resolved RAG-mediated DNA breaks in Atm-deficient lymphocytes target chromosomal breakpoints incis

Abstract: Canonical chromosomal translocations juxtaposing antigen receptor genes and oncogenes are a hallmark of many lymphoid malignancies. These translocations frequently form through the joining of DNA ends from double-strand breaks (DSBs) generated by the recombinase activating gene (RAG)-1 and -2 proteins at lymphocyte antigen receptor loci and breakpoint targets near oncogenes. Our understanding of chromosomal breakpoint target selection comes primarily from the analyses of these lesions, which are selected based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 35 publications
4
37
0
Order By: Relevance
“…Translocation partners for double-strand breaks are not strictly limited to closely interacting chromosome domains, but when a large number of doublestrand breaks is present, there is an increased frequency of interchromosomal translocation between partners with higher physical interaction 95 . All deep-sequencing studies to date have shown that double-strand breaks on the same chromosome, particularly those lying nearby on the same chromosome, have the highest rate of joining, and this matches a previous study of the frequency of joining of breaks induced by the V(D)J recombination-activating protein 1 (RAG1) and RAG2 recombinases 96 . Taking these studies together, the primary predictor for whether genes take part in translocations is the frequency with which those genes undergo doublestrand breakage.…”
Section: Factors Favouring Translocationssupporting
confidence: 69%
“…Translocation partners for double-strand breaks are not strictly limited to closely interacting chromosome domains, but when a large number of doublestrand breaks is present, there is an increased frequency of interchromosomal translocation between partners with higher physical interaction 95 . All deep-sequencing studies to date have shown that double-strand breaks on the same chromosome, particularly those lying nearby on the same chromosome, have the highest rate of joining, and this matches a previous study of the frequency of joining of breaks induced by the V(D)J recombination-activating protein 1 (RAG1) and RAG2 recombinases 96 . Taking these studies together, the primary predictor for whether genes take part in translocations is the frequency with which those genes undergo doublestrand breakage.…”
Section: Factors Favouring Translocationssupporting
confidence: 69%
“…S8). The bias for breakpoint targets at the IgLκ locus, which also undergoes inducible rearrangement in these cells, is reminiscent of what was observed for the aberrant resolution of coding ends in Atm-deficient abl pre-B cells (13,27). (13).…”
Section: −/−mentioning
confidence: 90%
“…One possibility is that these recurrent translocations arise at no more common frequency than any other translocation, but are selected on the basis of their potential to drive survival and proliferation of the cancer cell. An additional, long-standing hypothesis is that recurrent translocations arise because the translocation partners are in particularly close proximity in the nuclei of cells from the affected tissue 91, 92, 93 . Chromosome Conformation Capture has been used to measure genomic interactions, and combining this technique with deep sequencing has recently enabled the measurement at base-pair resolution of how closely genomic loci interact.…”
Section: Factors Favouring Translocationsmentioning
confidence: 99%